Social Aspects of Farm Forestry in Arid Zone - Bharara, L P; Sen, M L A (Annals of Arid Zone, 2016)
Social aspects of farm forestry have been discussed with reference to irrigation facility, ownership of land, form of settlement, vegetation and its use, nature and extent of species planted and those survived, preferences and place of planting in Sumerpur block of Pali district. There is a significant relationship between the number of trees planted and irrigation facility. Differences between’ the average number of trees planted by the households owning less than 20.0 and above 20 hectares of land are significant. Difference between the average number of trees planted by households living in compact, Dhani (scattered), and partial compact form of settlements, is not significant. Plantation is done mostly on field boundaries, irrigations wells, home compounds etc for shade, agricultural implements, fruits and food, animal feed etc. The survival variation ranges from 60.0 to 77.1 per cent.